Who is a Civilian in Gaza? Reflection on the Loss of Protection of Civilian Persons: An Interdisciplinary Treatise Focused on IHL with Military Strategy Aspects - Veronika D´Evereux; Vojtěch Sedlák (Obrana a Strategie)
The demand for significantly increased protection of civilians in the Gaza Strip from the consequences of Israeli military operations, together with reports of high civilian casualties, has resonated in public discourse for more than 18 months. The Gaza war, including its second phase involving ground operations, is regarded as an international armed conflict between the State of Israel and Palestine, particularly Hamas, which is considered the officially and legally elected authority in part of the Palestinian territory, the Gaza Strip, though not of Palestine as a whole. Civilian protection is thus assessed under the 1977 Additional Protocol I and international customary law. This paper explores the intersection of international humanitarian law and military strategy. Within these frameworks, and concerning military rules adopted by the State of Israel, it examines the issue of civilians losing protection from military attack. Focus is placed on distinguishing between civilians in Gaza who directly or indirectly participate in hostilities. The paper analyses the specifics of urban warfare, the obligation to minimise collateral damage, precautions in favour of civilians, and the challenges posed by the voluntary presence of civilians at military objectives. It aims to determine whether, and under what conditions, the IDF may lawfully launch a justifiable attack that also results in civilian casualties.